Implemen-ting Green IT through Virtualisation at the University of Canberra: A Case Study - Townsend, Tom; Mohammadian, Masoud (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Demand for Information Technology industry is increasing worldwide. The expansion of digital communication has seen a large growth in the use of IT and increased capacity for data collection, storage and processing for internal and external use in business and industry. IT demands at the university sector have been increasing rapidly with the introduction of new teaching and learning methods requiring anywhere anytime teaching and learning. Data centres have emerged as an approach that enables accesses to shared computing resources. However, the increasing trends of resource usage and cost of maintaining a large number of servers and electrical consumption within data centres are of a growing concern. There are several challenges and opportunities within a data centre realm to lower the resource usage and cost of data centres to improve the cost and energy efficiency. At the beginning of 2008, the University of Canberra (UC) completed a major re-organisation involving the centralisation of all IT departments. This case study looks at how virtualisation helped rationalise that dispersed environment and how virtualisation has continued to enable dramatic affects at UC. Topics covered include; how virtualisation has affected the physical Data Centre, how the management of the IT systems has changed and what benefits and challenges were realised.